Bioanalysis Young Investigator: Jia Li. (May 2011) - Li, Jia; Holmes, Elaine
Supervisor''s supporting comments I supervised Jia Li during her PhD research on the metabolic characterization of host––parasite interactions. Jia excelled at the analytical chemistry components of her thesis and specialized in the integration of multiplatform data (NMR, UPLC––MS, CE––MS and 454 data). Since obtaining her PhD (2009), she has achieved a prestigious Imperial College Junior Research Fellowship and has focused on applying data integration techniques to investigate mechanisms of bariatric surgery. To date she has 16 publications in journals including Proceedings of the National Academy of Sciences, Molecular Systems Biology and Gut, many as first author. Her achievements include the characterization of multicompartmental changes in Schistosoma mansoni infected mice and the metabolic characterization of bariatric surgery in rats. She used NMR spectroscopic analysis, hierarchical principal component analysis and partial least square discriminant analysis to create systems level models of parasitic infection, and subsequently developed a CE method to validate the biomarkers. For the bariatric surgery model she applied a combination of UPLC––MS and NMR methods for profiling biofluids and related them to changes in the fecal microbiome profiled using 454 sequencing. She has presented her work at international conferences and has developed a network of external collaborations. Jia is an excellent role model; she is genuinely innovative and motivated, and has a flair for analytical technology.